Investigations into Morphology and Mechanical Properties of Epoxidized Polystyrene/Polybutadiene/Polystyrene (SBS) Triblock Copolymer - Pandit, Rajesh; Youssef, Boulos; Saiter, Jean Marc; Adhikari, Rameshwar (Journal of Nepal Chemical Society, 2013)
An architecturally asymmetric polystyrene-block-polybutadiene-block-polystyrene (SBS) triblock copolymer possessing lamellar morphology was subjected to different degrees of epoxidation with performic acid generated in situ by the reaction between hydrogen peroxide and formic acid. The effect of the chemical modification on morphology and mechanical behaviour of the block copolymer was investigated by means of different techniques such as electron microscopy, Fourier transform Infrared (FTIR) spectroscopy, tensile testing and differential scanning calorimetry (DSC). It was found that the microphase separation behaviour and hence the mechanical properties of the materials can be drastically altered via epoxidation of the diene block of the styrene/diene triblock copolymers. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8057 Journal of Nepal Chemical Society Vol.28, 2011 Page 42-47 Uploaded date: May 7, 2013